Semi-virtual Plant for the Modelling, Control and Supervision of batch-processes. An example of a greenhouse irrigation system. Issue 29 (2015) - Rodríguez, F.; Castilla, M.; Sánchez, J.A.; Pawlowski, A.
Abstract: In this work, a hardware-software architecture for control engineering education is proposed and a case of study regarding a greenhouse irrigation virtual process has been implemented. This specific process is especially useful for subjects related to industrial automation, since it is characterized by mixed dynamics (continuous/discrete) and can be controlled by a Programmable Logic Controller (PLC). In such a case, there is no need to access to the real process that is not always available for practical exercises. Moreover, the developed scheme eliminates the maintenance costs related to real process, being a very important advantage for academic institutions. The developed architecture for the industrial process simulation uses Labview, OPC, MODBUS, SolidWorks and Schneider Modicon M340 PLC for the control of virtual processes. The developed example is applied to the greenhouse fertirrigation control that enables the agricultural engineering students to design the irrigation control system. The control strategy is implemented on the PLC which interacts with the virtual process by carrying out the necessary actions in order to control the appropriate variables of the process.